Improvement in physical properties of eroded agricultural soils through agronomic management practices - AHMAD, WIQAR; KHAN, FARMANULLAH; NAEEM, MUHAMMAD (The Indian Journal of Agricultural Sciences, 2014)
Arable land in Pakistan is shrinking due to construction of houses and development of infrastructure, there has been a trend of shifting agriculture towards steep lands in order to feed the increasing population. Soil erosion on these lands is one of the most significant ecological restrictions to sustainable agriculture. A study was conducted during 2006-2008 to test the agronomic management practices for mitigating the adverse effects of soil erosion on arable soil. The experiment was designed in RCB with split plot arrangements. Cropping patterns, i e maize (Zea mays L.)-wheat (Triticum aestivum L.)-maize (C1), maize-lentil (Lens culinaris Medic.)-maize (C2) and maizewheat+ lentil intercrop-maize (C3) were kept in main plots while fertilizer treatments; the control (T1), 50% NP also called farmers’ practice (T2), 100% NPK or the recommended dose (T3) and 20 tonnes/ha farmyard manure integrated with 50% mineral N and 100% P and K (T4) were kept in sub-plots. Fertilizer treatments significantly improved soil physical properties in both depths. T4 showed the maximum improvement (13, 12, 22 and 31%) in bulk density, porosity, saturation and available water over the control and 3, 3, 8 and 7% over the T3 in surface soil. Cereal-legume rotation showed the maximum improvement while significant improvement in soil physical properties was noted with time, i e from kharif 2006 to rabi 2007. Highly significant negative correlation was observed between bulk density and saturation percentage (r2=0.97) and bulk density and AWHC (r2=0.93). It was concluded that NPK fertilizer alone cannot restore the physical environment of eroded soil to its maximum limit, but this objective could, rather, be achieved through mixed application of farmyard manure and mineral fertilizers. For this purpose, being an unstable nutrient element, recommended dose of mineral N must be reduced by 50% to avoid its over-application. In addition to other benefits of legumes in rotation, its improvement of physical properties further assert their importance in farming on such eroded lands.